Peran Istighasah dalam Mengurangi Kecemasan Siswa menghadapi Ujian Nasional di UPTD SMAN I Mojo Kediri: Kajian Fenomenologis Psikosufistik Pendidikan Islam - Fuadah, Ainani (Didaktika Religia, 2014)
Istighathah, on the day before UN, has been a religious culture in SMAN 1 Mojo.This istighathah is supported by various parties ranging from the school, the viceprincipal, the teachers, the UN committee and all UN participants. This existence,for Sufi Psychology, which contains dhikir (remembrance) reading and prayer cannormalize function of neural network systems, cells and organs throughout thebody. In the world of Sufism, istighathah with remembrance has an importantposition in an effort to draw closer to Allah SWT. And this istighathah has becomeroutine annually before the administration of UN. This is because istighathah ashield that can provide encouragement for every human being to be serious intrying and praying and not easily discouraged when facing failure in UN. Theresults of this study are, first, istighathah at SMAN 1 Mojo has become routinebefore UN, either daily or collectively. There is a belief possessed by most studentsof SMAN 1 Mojo that can reduce the anxieties in which the result can producecalmness physically and mentally when they are facing UN.